2016
DOI: 10.1002/nme.5239
|View full text |Cite
|
Sign up to set email alerts
|

Post‐buckling optimization of composite structures using Koiter's method

Abstract: SUMMARYThin-walled structures, when compressed, are prone to buckling. To fully utilize the capabilities of such structures, the post-buckling response should be considered and optimized in the design process. This work presents a novel method for gradient based design optimization of the post-buckling performance of structures. The post-buckling analysis is based on Koiter's asymptotic method. To perform gradient based optimization, the design sensitivities of the Koiter factors are derived and new design opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…where the tangent stiffness K t R is calculated by the derivative of the load multiplier vector with respective to the generalized displacement , and its analytical expression can be obtained directly, as given by (13). 2.…”
Section: The First Path-following Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…where the tangent stiffness K t R is calculated by the derivative of the load multiplier vector with respective to the generalized displacement , and its analytical expression can be obtained directly, as given by (13). 2.…”
Section: The First Path-following Stepmentioning
confidence: 99%
“…The reduced-order modeling methods [11][12][13][14] proposed based on Koiter perturbation theory 15 offer an alternative to markedly reduce the number of degrees of freedom in large-scale finite element models. The main feature of the Koiter reduction method 16,17 is to construct the reduced-order model at the bifurcation point by representing the displacement field to be an approximate superposition of buckling modes, thus the range of validity of the reduced-order model is limited to the initial postbuckling stage and the prebuckling nonlinearities cannot be considered very well.…”
mentioning
confidence: 99%
“…However, given the practical significance of Koiter's theory in the problem of structural stability and given the attempts of its FE implementation since early 1970s [9], it is still unavailable from any mainstream commercial FE code, for which disappointment is an understatement. As a result, the research activities on Koiter's theory declined, given sparsely populated publications [10][11][12][13][14][15][16][17][18][19][20][21][22][23] as a representative spectrum of them from various perspectives, without occupying the length of this paper for a comprehensive literature review while a reasonable coverage can be found in relatively recent publications [24,25]. The reality is that for, most structural designers and analysts, Koiter's theory is becoming distant past instead of useful tool at their fingertips.…”
Section: Introductionmentioning
confidence: 99%
“…The asymptotic theory originally proposed by Koiter [1] allows a rapid evaluation of the initial post-buckling behavior of structures. The method has been used within a semianalytical context [2,3] and has also been applied within a finite element framework [4,5,6,7,8,9,10,11,12,13,14,15,16]. In recent years, the method has been applied in the context of variable stiffness of panel-type structures [17,18,14,16,19,20] and in the analysis of imperfection sensitive shells [21,22,23].…”
Section: Introductionmentioning
confidence: 99%